Sound Absorption Study Of Three-Dimensional Printed Micro-Perforated Panel - Ibrahim, Nazri (Universiti Sains Malaysia, 2018)
Micro-perforated panel is widely used to absorb sound and reduce the sound intensity. It is called ‘next-generation’ sound absorber as it more environmental-friendly the existing porous sound absorbent materials. Micro-perforated panel is commonly used in hospitals, infant and dining facilities. A new method to produce micro-perforated panel is introduced, which is three-dimensional printing method. The main objective of this project is to study the sound absorption coefficient of three-dimensional printed micro-perforated panel. This objective is done theoretically and experimentally. The sound absorption coefficient of micro-perforated panel varies with the sound frequencies is determined by using MATLAB and impedance-tube test. The experimental results are verified with the simulation results and the percent difference of the results are calculated. The sound absorption coefficient of micro-perforated is then studied with the effect of sound incidence angle. The results can determine which sound incidence angle produce the most effective micro-perforated panel based on the sound absorption coefficient measured.